Clinical Characteristics and Ancillary Test Results Among Patients With Botulism—United States, 2002–2015. (27th December 2017) - Rao, Agam K; Lin, Neal H; Jackson, Kelly A; Mody, Rajal K; Griffin, Patricia M
Abstract: Background: Botulism is classically described as a bilateral, symmetric, descending flaccid paralysis in an afebrile and alert patient without sensory findings. We describe the reported spectrum of clinical findings among persons >12 months of age in the United States during 2002–2015. Methods: The Centers for Disease Control and Prevention collects clinical findings reported by physicians treating suspected cases of botulism nationwide. We analyzed symptoms and signs, and neuroimaging and cerebrospinal fluid (CSF) results. A case was defined as illness compatible with botulism with laboratory confirmation or epidemiologic link to a confirmed case, and presence or absence of at least 1 sign or symptom recorded. Physicians' differential diagnoses were evaluated. Results: Clinical information was evaluated for 332 botulism cases; data quality and completeness were variable. Most had no fever (99%), descending paralysis (93%), no mental status change (91%), at least 1 ocular weakness finding (84%), and neuroimaging without acute changes (82%). Some had paresthesias (17%), elevated CSF protein level (13%), and other features sometimes considered indicative of alternative diagnoses. Five of 71 (7%) cases with sufficient information were reported to have atypical findings (eg, at least 1 cranial nerve finding that was unilateral or ascending paralysis). Illnesses on the physician differential included Guillain-Barré syndrome (99 cases) and myasthenia gravis (76 cases) and, rarely, gastrointestinal-related illness (5 cases), multiple sclerosis (3 cases), sepsis (3 cases), and Lyme disease (2 cases). Conclusions: Our analysis illustrates that classic symptoms and signs were common among patients with botulism but that features considered atypical were reported by some physicians. Diagnosis can be challenging, as illustrated by the broad range of illnesses on physician differentials. Abstract : Botulism is classically described as a bilateral, symmetric, descending flaccid paralysis in an afebrile and alert patient without sensory findings. In our analysis, the classic symptoms and signs were common among patients with botulism, but features considered atypical were reported and could affect suspicion for botulism.